Glass shape influences the flavour of beer - Mirabito, A; Oliphant, M; Van Doorn, G; Watson, S; Spence, C (Elsevier, 2017)
It is often said that our perception of wine varies as a function of the receptacle in which it is presented. Indeed, glassware has been the subject of extensive study in this category. By contrast, the impact of glassware on the perception of beer has been largely ignored in the field of sensory science research. The current study was specifically designed to investigate the influence of the shape (specifically side curvature) of the glass on people's perception of beer. Fifty-three Australian participants rated (on 10-point Likert scales) a beer presented in one of two glasses. The beer was perceived as being fruitier and more intense when served in a curved-sided glass. Given previous research showing that people match fruitiness with curvature (rather than straightness/angularity), these results fit within the existing literature on crossmodal correspondences between shape and taste properties.